2010
DOI: 10.1158/1078-0432.ccr-09-2610
|View full text |Cite
|
Sign up to set email alerts
|

Activation of β-Catenin by Hypoxia in Hepatocellular Carcinoma Contributes to Enhanced Metastatic Potential and Poor Prognosis

Abstract: Purpose: Aberrant activation of β-catenin contributes to the malignant phenotype in hepatocellular carcinoma (HCC). Hypoxia is also known to promote HCC invasion and metastasis. However, the association between β-catenin and the proinvasive role of hypoxia remains unclear. We investigated the role of β-catenin in the proinvasive consequences of hypoxia in HCC.Experimental Design: We established in vitro and in vivo hypoxic models to investigate the expression of β-catenin in hypoxic HCC cells and its role in h… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
117
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 166 publications
(126 citation statements)
references
References 29 publications
6
117
0
Order By: Relevance
“…Numerous studies have reported that β-catenin overexpression in the cytoplasm and/or nucleus is correlated with cancer metastasis and poor prognosis (43)(44)(45)(46)(47)(48)(49)(50)(51). In the present study, higher Edmondson grade, poor TNM stage and positive portal vein invasion cases were identified to have increased cytoplasmic expression of β-catenin.…”
Section: Fak β-Catenin C-met Clinicopathological --------------------supporting
confidence: 55%
“…Numerous studies have reported that β-catenin overexpression in the cytoplasm and/or nucleus is correlated with cancer metastasis and poor prognosis (43)(44)(45)(46)(47)(48)(49)(50)(51). In the present study, higher Edmondson grade, poor TNM stage and positive portal vein invasion cases were identified to have increased cytoplasmic expression of β-catenin.…”
Section: Fak β-Catenin C-met Clinicopathological --------------------supporting
confidence: 55%
“…This expression pattern was accompanied by changes in E-cadherin expression, suggesting that b-catenin plays an important role in the metastasis of colorectal cancer, participating in EMT at the invasive front and in MET in metastases (13,55). In support of these findings, it was observed that silencing b-catenin in hypoxic MHCC97 and Hep3B cells also reversed EMT (56). Using a variant of the human cell line LIM1863 (LIM1863-Mph), Vincan and colleagues (57,58) established a unique model of colorectal cancer morphogenesis and showed that FZD7 plays a pivotal role in phenotype transitions, suggesting that Wnt signaling participates in orchestrating colorectal cancer morphogenesis.…”
Section: Mechanism Of Metmentioning
confidence: 59%
“…All these studies have shown that β-catenin is highly expressed in the above tumor tissues. In liver cancer cells, Wnt/β-catenin signaling pathway can promote the invasion and metastasis of cells through enhancing the hypoxia-induced epithelial-mesenchymal transition, and the expression of β-catenin is negatively correlated with the survival duration of patients after resection [25,26]. Also, in colorectal cancer cells, hypoxic environment can facilitate cell growth and invasion through activation of Nur77-β-catenin loop [27].…”
Section: Discussionmentioning
confidence: 99%